'A Formula Which I Derived Many Years Ago' Boole, Reichenbach and Popper on Probability and Conditionals. Issue 4 (2nd October 2022) - Rott, Hans
Abstract : This note presents a very brief history of the observation that the probability of the material conditional A ⊃ B is in general different from, but cannot be less than, the conditional probability of B given A . The difference between the two probabilities is significant for the interpretation of conditionals and for the possibility of inductive probability. It can be quantitatively specified in so-called 'excess laws' for which Popper appears to have claimed priority. I argue that such a priority claim should be rejected and credit should instead be given, if to anyone, to Boole and Reichenbach instead.